Tinjauan Penyebab Pengembalian Berkas Klaim Biaya Pelayanan Pasien Rawat Inap BPJS Kesehatan di Rumah Sakit Pelabuhan Jakarta Tahun 2022 - Siti Rahmawati Handayani; Lily Widjaja; Daniel Happy Putra; Dina Sonia (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
In the process of submitting a BPJS Health Claim, some requirements must be completed by the Health Facility. Of these requirements, the BPJS Health party will know that the claim submission can be paid or returned/delayed. This research was conducted to find out the reasons for returning the claim file for BPJS Kesehatan inpatient care at the Jakarta Harbor Hospital in 2022. The method in this study used descriptive research with a quantitative approach. The results of the study were 118 samples (6.7%) of 1,762 files, the highest returned cause was an inaccuracy in the coding of diagnoses/actions of 49 (42%), and the second highest was not fulfilling inpatient administration 18 (15%), other causes - others as much as 51 (43%). 3 factors from 5M are the cause of returning claim files, namely the human factor: casemix officers who are not diligent, lack of coder understanding/knowledge, and lack of accuracy in the filing department so that files are missed/left behind, machine: there is an upgrade to the latest version of the INA-application CBGs and V-Claim are also the Ministry of Health's newest program which requires TB patients to be inputted into the SITB application, Material: incomplete claim requirements files. While the money and method factors are not an obstacle or a cause for returning claim files. It is recommended to evaluate and re-socialize the reasons for returning BPJS Health claims so that the process of submitting BPJS Health claims is carried out properly and is 100% accepted.